2002
DOI: 10.1093/milmed/167.11.893
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Virtual Reality Simulator in Sustainment Training

Abstract: Is there a better way to train and prepare our health care personnel to function in a chemical biological environment while continuing to provide for patient care in a variety of healthcare settings? The purpose of this pilot work was to compare the effectiveness and user satisfaction of the Cath-Sim Intravenous Training System to the traditional IV arm model for teaching and achieving competence at IV insertion while in Mission-Oriented Protective Posture level 4 for Army medical personnel. Grounded in adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The recent development of technologic advances in the area of medical education provides a powerful platform for advancing the cognitive and psychomotor skills of practitioners. A large number of computer‐based simulators have been introduced in teaching clinical practice 7,10–12 . Although many of these devices are highly realistic, their educational value is under investigation, especially in terms of their learning curve assessment and role within a training curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of technologic advances in the area of medical education provides a powerful platform for advancing the cognitive and psychomotor skills of practitioners. A large number of computer‐based simulators have been introduced in teaching clinical practice 7,10–12 . Although many of these devices are highly realistic, their educational value is under investigation, especially in terms of their learning curve assessment and role within a training curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…All but one study demonstrated a positive association between higher fidelity and process skills (effect size = À0.63 to 0.70, five studies), and the single study with negative effect sizes had positive associations with both learner reactions and time skill outcomes. 25 Likewise, higher fidelity was associated with uniformly better time outcomes (effect size = 0.31 to 1.36, three studies). Only one study measured patient effects, 26 and although it reported moderate benefits to learning (effect size = 0.57), the comparison curriculum differed in more than just the level of fidelity.…”
Section: Comparison Between Alternate Types Of Technologyenhanced Simmentioning
confidence: 91%
“…There were 19 studies that used designs in which one approach to simulation-based education was compared with another (see Table 3). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Twelve of the 19 studies included prehospital providers as participants, and nine of these studies focused on airway management training. Because the research questions in these 19 studies varied substantially, we were unable to provide a quantitative synthesis of results.…”
Section: Comparison Between Alternate Types Of Technologyenhanced Simmentioning
confidence: 99%
See 1 more Smart Citation
“…Lasome, Flaherty, & Torrance, 2002;Ahlberg, Hultcrantz, Jaramillo, Lindblom, & Arvidsson, 2005; D Alverson et al, 2005;Caudell et al, 2003;. Colt, Crawford, & Galbraith, 2001;Goolsby, Simulation and Short Course Programs…”
mentioning
confidence: 99%